Africa's world trade Informal economies and globalization from below - Lee, Margaret C. (Africa Now, 2014)
Are Africa's world markets really contributing to development across the continent for individuals, nations and regions? This is the key question posed by Margaret Lee in this provocative book, in which she argues that all too often the voices of African traders are obscured amid a blizzard of statistical analysis. However, it is these very voices - from those operating on the ground as formal or informal traders - that must be listened to in order to form a true understanding of the impact trade regimes have on these individuals and their communities. Featuring a wealth of oral histories from across sub-Saharan Africa and beyond, including Africans in China, Africa's World Trade offers a unique insight into how the complexity of international trade agreements can shape the everyday lives of ordinary Africans.